Total Phenolic Content and Antioxidant Activity of Anthocyanin Extract from Purple Yam (Dioscorea alata L.) Flour Using Different Solvents - Tamaroh, Siti; Raharjo, Sri; Murdiati, Agnes; Anggrahini, Sri (Pakistan Journal of Nutrition, 2018)
Background and Objective: Purple yam (Dioscorea alata L.) is a potential source of natural antioxidants due to its relatively high anthocyanin content. Anthocyanin is a natural source of antioxidants, acting as a free radical scavenger with a role in aging, cancer and degenerative illness prevention. Using a variety of solvents and acids, this study aimed to extract purple yam flour anthocyanins with high antioxidant activities. Methodology: Anthocyanins were extracted using methanol and ethanol-based solvents that were acidified with hydrochloric acid (HCl), citric acid or tartaric acid. The resulting extracts were assayed for anthocyanin and total phenolic contents, antioxidant activity (expressed as % radical-scavenger activity [%RSA]) and ferric reducing antioxidant power (FRAP). All data were analyzed using one-way analysis of variance. The differences were analyzed using Duncan’s multiple range test. The p<0.05 was considered significant. Pearson’s correlation coefficient analysis among anthocyanins, total phenolics contents and antioxidant activities were calculated using Microsoft Excel, 2007. Results: Results showed that the methanol/HCl (MeH) solvent could be used to extract anthocyanin from purple yam flour more thoroughly than other solvents. Total phenolic contents were not significantly different between MeH and methanol/tartaric acid (MeT) extracts (5.18 mg GA/100 g extract). Antioxidant activities of MeH and MeT anthocyanin extracts were not significantly different (69.87% RSA and FRAP of 50.27 μmol ε ferro L–1). Anthocyanin and total phenol contents correlated significantly with RSA and FRAP. Conclusion: This study suggested that anthocyanins and phenols purple yam flour are an abundant natural antioxidant sources, while the best solvent for the extraction was an acidified polar solvent.